The Spillover (and Direct) Effects of Workplace Contact on Intergroup Attitudes - Jensen, Robert (The Review of Economics and Statistics, 2026)
Can workplace contact with outgroup members affect attitudes towards that group? If so, can this spread to others within a social network? We randomly assigned Hindu job applicants in India either a Hindu or Muslim partner for training and placement in call center jobs. One year later, those applicants assigned Muslim partners expressed more positive attitudes towards Muslims, were more likely to say Muslims faced discrimination and had greater knowledge of Islamic practices. Close friends and family members of those workers also experience similar, though smaller, changes, despite reporting no additional direct contact with Muslims.